Exploring Inclusive Education and Education for Sustainable Development in A Community Education Study Program - Muryanti; Pahmi; Gianini Sonnevil (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
While inclusive education and Education for Sustainable Development (ESD) are promoted in higher education policy, little is known about how these two agendas are understood and enacted within a study program. To address this gap, this study explores the implementation of the two agendas at the study program level in a Community Education Study Program using a qualitative case study approach. Data were collected purposively from two sources: semi-structured interviews with two program leaders and two lecturers at the study program, and document analysis of the 2022 and 2025 curriculum documents. Both data sets were coded using thematic analysis. The findings show that while participants are aware of inclusive education and ESD, their conceptual understanding remains fragmented and tends to focus on access and community engagement. Document analysis revealed that aspects of inclusion and sustainability are present in curriculum documents, but they are mostly implicit. However, teaching practices show more dynamic implementation, as lecturers applied community-based learning that aligned with ESD, despite not being systematically documented. The study also found that the implementation seems to be initiated by individual lecturers rather than explicitly regulated. By understanding the implementation of the agendas within one institutional case, this study contributes to the literature on policy enactment in higher education, highlighting where the policy-practice gap emerges.